Malignant melanoma in Rome, Italy, 1970-9. Issue 1 (March 1985) - Petrelli, G; Maggini, M; Taggi, F; Morpurgo, G
Abstract : An epidemiological study was conducted in the city of Rome and the incidence of malignant melanoma was determined retrospectively for the years 1970-9. All patients had legal residence in Rome and a histological diagnosis of melanoma during that period; only cases of malignant melanoma of the skin (ICD 172, 8th revision) were considered. A total of 17 public and 82 private hospitals were involved in the study with 11 081 and 6127 hospital beds respectively. All the hospitals in the study had one of the following therapeutic and diagnostic facilities: internal medicine, dermatology, oncology, radiology, surgery, plastic surgery, histopathology. Analyses of incidence are based on 500 cases, 237 males and 263 females, collected in the period 1970-9. The data indicate a positive time trend in incidence; the average annual increase is 0.27 cases/year per 100 000. The data show that in a Mediterranean and Latin country such as Italy the incidence of melanoma presents the same ascending trend as that of other Caucasian countries, whether European or not, the slope of the curves is similar for both sexes. The distribution of the primary site for both sexes is closely parallel to that described for all Caucasian populations, the lower limbs being more affected in females and the trunk in males.